STRATEGI PEMBELAJARAN DIRECT INTRODUCTION PADA ANAK BERKEBUTUHAN KHUSUS TUNA GRAHITA DI SLB-E NEGERI PEMBINA TINGKAT PROVINSI SUMATERA UTARA - Mukti, Muhammad Akbar; Kurnia, Dian; Muaya, Citra Dewi; Ramadhan, M. Rizky; Sundari, Sundari; Sovia, Sovia; Pharama, Tiara Eka (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2024)
Children with intellectual disabilities who have limitations and deficiencies in terms of intelligence also have the right to receive education. One of the education provided to children with intellectual disabilities is in the form of a special self-development program with the aim of fostering children's independence. Moderate intellectual disabilities have limitations in the ability to care for themselves, take care of themselves, help themselves, life skills, etc. The research method in this study uses a descriptive qualitative approach research method, while the data collection process in this study uses observation, interview, and documentation techniques. This research was conducted on Monday, December 4, 2023 at 08.00 to 12.00 WIB. The location of the research was carried out at the SLB-E Negeri Pembina, North Sumatra Province, precisely in class XI-1C. The learning strategy for ABK with intellectual disabilities is of course we choose a learning strategy that suits them, because ABK with intellectual disabilities must carry out learning with an individual approach if now using the independent curriculum, actually ABK with intellectual disabilities have been independent learning for a long time. The direct introduction learning strategy for children with special needs and mental retardation is quite effective and can be used as an alternative for children with special needs and mental retardation in carrying out their learning activities.